2016
DOI: 10.1097/ncc.0000000000000263
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Evidence-Based, Nurse-Led Psychoeducational Intervention With Peer Support in Gynecologic Oncology

Abstract: The Medical Research Council framework is useful in developing nursing interventions. The specific methods and strategies described are useful for designing future complex studies targeting patient supportive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…In addition to information from healthcare professionals, some participants may have shared the information about side effects with other patients because a number of them had been on the ward for some time. Peer support has been shown to be useful in psycho-educational support programmes targeting patients with cancer 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to information from healthcare professionals, some participants may have shared the information about side effects with other patients because a number of them had been on the ward for some time. Peer support has been shown to be useful in psycho-educational support programmes targeting patients with cancer 15 .…”
Section: Discussionmentioning
confidence: 99%
“…First, contemporary cancer treatment is becoming increasingly complex and individualized, characterised by constant advances in therapy such as treatments relying on molecularly targeted agents and immunotherapies that require the adoption of a more personalised approach to care (Clauser et al, 2011). Second, the continuing shift from hospitalised cancer care to outpatient-based care has promoted the development of more independent roles for nurses, including symptom management and follow-up interventions (Bergin et al, 2016, Latter et al, 2017. Third, the specialty of cancer nursing has expanded rapidly, driven in part by current fiscal challenges in the global economy and a range of workforce pressures within the field of oncology, but also in response to the changing demographics and expectations of people living with, beyond, or at risk of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty‐four studies were used to generate the theory that training in survivorship care should be provided to relevant healthcare professionals so they are sufficiently prepared to communicate survivorship information and direct survivors to appropriate support services 22,24,25,27,28,30,33,34,36,38,39,41,42,44,46,47,50,51,55–60 . In a study assessing barriers to providing survivorship care, hematology cancer nurses reported prioritizing clinical treatment over survivorship as they felt inadequately trained to deliver survivorship information 38 .…”
Section: Resultsmentioning
confidence: 99%